Effects of root restriction and mycorrhiza inoculation on growth, physiological and yield responses of chilli grown in soilless culture - Zakaria, Nurul Idayu (2018)
Chilli (Capsicum annuum L.) that is used in food preparation for its flavour, aroma, and colour is a fruit vegetable with a high economic value that is cultivated in soilless culture in Malaysia. In soilless culture, the use of high substrate volume of about 6 to 8 liters per plant is closely related to increases in water usage, fertilizer and manpower. Meanwhile, the rising price of substrate and fertilizers coupled with pollution threat due to the disposal of used substrate in the large scale commercial production area results in higher production cost. Therefore, an approach to optimize the volume of substrate and concentration of fertilizer in small container could potentially reduce the production cost in soilless culture meanwhile by understanding physiological mechanism of the growth reduction, root system manipulation by using beneficial microbes such as mycorrhiza could potentially be adopted to improve yield under restricted root condition. Thus, the growth and yield responses of chilli plants grown in small containers were tested using six sizes of polybags. The result from this study showed reductions of stem diameter and total plant biomass of chilli grown in horizontal polybag of 17 cm in length with 32% yield reduction which is associated with root restriction compared to 31.7% yield increment in horizontal polybag of 27 cm in length. The next experiment was conducted to determine the optimum fertilizer concentration in different container sizes chosen from the previous study. Here the effects of 1.5 and 2.5 dS/m fertilizer concentration subjected to different container sizes of 2805 cm³, 6831 cm³ and 10557 cm³ on growth, physiological response and yield of chilli were determined. The result showed reduction of vegetative growth with 24% and 17% reduction of fruit fresh weight in 1.5 dS/m fertilizer concentration and in 2805 cm